Design, Synthesis and Screening of Newer-8-Hydroxy Quinoline Derivatives as Novel Anti Tubercular Agents - Surekha, S R; Joseph, Lincy; George, Mathew (International Journal of Applied Sciences and Biotechnology, 2014)
A series of 8-hydroxyquinolines are synthesized and their Antitubercular, antifungal, and antibacterial activities are tested. Quinolines are found to possess antibacterial, antifungal, immunosuppressive, analgesic, vasorelaxing, Antiplasmodial, anticancer and PDE4 inhibitory activities. Aryloxypropanolamines were reported to be associated with β-adrenergic blocking, CNS depressant and hypotensive activities. In view of the potential nature of these moieties it was considered worthwhile to study the effects of two pharmacophoric moieties such as quinoline and propanolamines/amino ethane in a single molecule. In the present study the synthesis, antitubercular, antifungal, and antibacterial activities and structure activity relationship of aryloxypropanolamine substituted 8-hydroxy quinolines are reported. The compounds were characterized by IR, H-NMR, spectral and Elemental analysis. DOI: http://dx.doi.org/10.3126/ijasbt.v2i3.11100 Int J Appl Sci Biotechnol, Vol. 2(3): 342-358